Integrated approach of splint, face and full-body yoga, and smartphonebased cognitive behavioral therapy for temporomandibular disorder: A case report - Annisa Athirah; Ismet D. Nasution; Ricca Chairunnisa (Indonesia Prosthodontic Association, 2025)
ABSTRACT Background: Temporomandibular disorders (TMD) can result from stress, occlusal imbalance, trauma, and poor posture. Stress often triggers parafunctional habits such as clenching, leading to masticatory muscle hyperactivity, fatigue, stiffness, and pain radiating to the head and other body regions. Conservative therapies include splints, yoga, and cognitive behavioral therapy (CBT). Objective: To report the management of a TMD case diagnosed as myofascial pain with spreading and arthralgia using a combination of stabilization splint, face and full-body yoga, and smartphone-based CBT. Case Report: A 28-year-old female presented with muscle pain radiating to the head, neck, and lower back, and limited mouth opening. She had a history of clenching. DC/TMD Axis I confirmed myofascial pain with spreading and arthralgia; Axis II showed mild depression (score = 6). Treatment comprised a stabilization splint, face and full-body yoga, and smartphone-based CBT over six weeks. Post-treatment, mouth opening increased from 25 mm to 33 mm, depression score decreased to 1, and muscle tension was significantly reduced. The patient reported improved quality of life and awareness of parafunctional habits. Conclusion:A multidisciplinary approach integrating splint therapy, yoga, and smartphone-based CBT effectively reduces TMD symptoms. Splints and yoga relax muscles, while CBT enhances stress management and awareness of clenching, contributing to therapeutic success. Keyword: Myofascial, face yoga, full-body yoga, clenching, cognitive behavioral therapy (CBT)